Hubungan Antara Konsumsi Ikan Asin Dengan Karsinoma Nasofaring - Retno Julianingrum (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; nasopharyngeal carcinoma (NPC) is the most common malignancy of the ear, nose, and throat (ENT). Aim was to determine the relationship between salted fish consumption and nasopharyngeal carcinoma. Method; Search for articles was carried out in PubMed® with related keywords and then filtered according to inclusion and exclusion criteria. So that we get six articles that are relevant for a critical assessment. Result; that the association between salted fish consumption and nasopharyngeal carcinoma was inconsistent. Conclusion; differences in the incidence of nasopharyngeal carcinoma and salted fish are eaten in different populations may have contributed to this inconsistent outcome. To find better evidence, we recommend the use of a systematic review